2022
DOI: 10.1186/s12917-022-03307-3
|View full text |Cite
|
Sign up to set email alerts
|

Pycnogenol a promising remedy for diabetic keratopathy in experimentally induced corneal alkali burns in diabetic rats

Abstract: Aim This study aimed to investigate the efficiency of topically applied pycnogenol (PYC) in healing the standardized alkaline corneal ulcer in diabetic and normal rats. Materials and methods The corneal alkali-burn injury (CA-I) model was unilaterally developed in Wistar rats by filter paper saturated with 0.01 M of NaOH and touching the eyes for 45 s. Rats were divided into four groups: Normal control (NC), normal PYC (NPYC), diabetic control (DC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The main clinical manifestations are dry eye, decreased corneal sensitivity, difficult healing of the corneal epithelium after ocular surgery or trauma, neurotrophic corneal ulcers, etc. The main pathological mechanism of diabetic keratopathy could be stem cell dysfunction, abnormal function of the corneal epithelium, abnormal components in the basement membrane, deposition of the product of glycosylation, injury to the corneal nerve endings, abnormal corneal endothelium, oxidative stress, or inflammatory response (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…The main clinical manifestations are dry eye, decreased corneal sensitivity, difficult healing of the corneal epithelium after ocular surgery or trauma, neurotrophic corneal ulcers, etc. The main pathological mechanism of diabetic keratopathy could be stem cell dysfunction, abnormal function of the corneal epithelium, abnormal components in the basement membrane, deposition of the product of glycosylation, injury to the corneal nerve endings, abnormal corneal endothelium, oxidative stress, or inflammatory response (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…Pycnogenol (PYC), a standardised extract of French maritime pine bark (Pinus pinaster Aiton), contains several active components, including proanthocyanins. PYC, which is used worldwide as an herbal remedy and as a nutritional and dietary supplement for the management of various disorders including inflammatory and circulatory diseases, has antioxidant, anti-inflammatory, anticancer, and antimicrobial effects (Torras et al 2005;Yang et al 2014;Hamed et al 2022;Nattagh-Eshtivani et al 2022). PYC is also used to manage respiratory diseases like asthma, rhinitis, pulmonary fibrosis, and chronic obstructive pulmonary disease (Wilson et al 2010;Liu et al 2016;Shin et al 2016;Park et al 2022).…”
mentioning
confidence: 99%
“…It has been reported that during prolonged hyperglycemia, glucose causes auto-oxidation of proteins and induces the production of ROS ( 28 ). High glucose levels decrease the antioxidant defense and enhance oxidative stress in cells ( 29 ). After a corneal injury, in diabetic mice, inflammation and oxidative stress greatly limit the healing of the corneal epithelium and increase the risk of persistent defects of the corneal epithelium ( 1 , 2 ).…”
Section: Discussionmentioning
confidence: 99%